2014
DOI: 10.1111/nin.12064
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of social justice intent in photovoice research studies from 2008 to 2013

Abstract: In an age where digital images are omnipresent, the use of participant photography in qualitative research has become accessible and commonplace. Yet, scant attention is paid to the social justice impact of photovoice among studies that have used this innovative method as a way to promote social justice. There is a need to review this method to understand its contributions and possibilities. This literature review of photovoice research studies 1) explores whether authors implicitly or explicitly related the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 57 publications
2
81
0
1
Order By: Relevance
“…Most capacity‐building activities occurred at the individual level. These findings are consistent with other housing‐related photovoice studies that faced similar challenges in reaching systemic change (Grieb et al., ; Halifax, Yurichuk, Meeks, & Khandor, ; Parker et al., ; Sanon, Evans‐Agnew, & Boutain, ). Recommendations to facilitate system‐level change through participatory research include inviting policy stakeholders to participate (Sanon et al., ), hosting trainings on the policy‐making process, working with policy mentors, and using mass media to advance policy awareness (Postma et al, ; Minkler et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…Most capacity‐building activities occurred at the individual level. These findings are consistent with other housing‐related photovoice studies that faced similar challenges in reaching systemic change (Grieb et al., ; Halifax, Yurichuk, Meeks, & Khandor, ; Parker et al., ; Sanon, Evans‐Agnew, & Boutain, ). Recommendations to facilitate system‐level change through participatory research include inviting policy stakeholders to participate (Sanon et al., ), hosting trainings on the policy‐making process, working with policy mentors, and using mass media to advance policy awareness (Postma et al, ; Minkler et al., ).…”
Section: Discussionsupporting
confidence: 90%
“…With the rise of digital photography, the ability to collect participant-generated photographs in qualitative research has "become accessible and commonplace" (Sanon et al 2014). Common participant-generated visual methodologies that use photographs include Photo-elicitation, PhotoStory, and Photovoice.…”
Section: Visual Research Methods-photographymentioning
confidence: 99%
“…A criticism of photovoice that emerged from a comprehensive review of recent studies is a lack of focus on ameliorative social justice impact. Although increased awareness is an important element of photovoice, efforts toward actions that mitigate factors that lead to unjust conditions are critical (Sanon et al, 2014). Therefore, in our study, we used participant‐identified advocacy items to inform the agenda of the community forum, linking research to transformative policy change.…”
Section: Resultsmentioning
confidence: 99%
“…After the identification of a particular priority reached through engagement with the community, researchers invite participants to document salient experiences through photography and to share and reflect on these photographs in a series of large‐group discussions. Photovoice is specifically designed to enable participants to reach policy makers (Wang & Redwood‐Jones, 2001), with an important consideration in reporting findings being the dissemination of qualitative results and photographs to the larger community to promote change (Sanon, Evans‐Agnew, & Boutain, 2014). A comprehensive review of studies using photovoice supports its application as an effective methodology for facilitating community change (Hergenrather et al, 2009) and as an innovative practice for counseling research (Smith, Bratini, & Appio, 2012).…”
Section: Photovoicementioning
confidence: 99%